Building Sustainable Digital Education in India: Transformation through Equity, Inclusion and Accessibility - Rajiv Kumar Singh; Alka Singh (Unit Publikasi Ilmiah, P3M, Politeknik Negeri Bali, 2024)
In the contemporary world, sustainable digital transformation involves the judicious application of innovative technologies to enhance the current and future well-being of individuals. This paper explores the transformative trajectory of India's digital policies, such as Aadhaar, Jan-DhanYojna, Bharat Net, and Digital India, demonstrating a dedicated commitment to digital inclusion. However, the World's largest open schooling system, the National Institute of Open Schooling (NIOS), strategically harnessed the technology to enhance equity, inclusion, and accessibility in education. The paper delves into the intersection of digital transformation and education, emphasizing its potential to revolutionize the learning experience, empower learners, and engage society. NIOS's systematic and academic digital initiatives emphasize the importance of e-governance, innovation, and the integration of digital platforms and resources. Through e-governance and innovative approaches, NIOS has streamlined administrative processes, improved transparency, and enhanced accessibility for learners. Academic transformation concentrates on reshaping pedagogical approaches and content delivery. The paper also addresses eSchools' potential to redefine education landscapes and the need for research and development to push the boundaries of digital education. This paper presents insights that contribute to the ongoing discourse on leveraging digital transformation to achieve access to equitable and inclusive education on a global scale.